Inter-organ metabolic interaction networks in non-alcoholic fatty liver disease - Fan, Yu-Hong; Zhang, Siyao; Wang, Ye; Wang, Hongni; Li, Hongliang; Bai, Lan (Frontiers in Endocrinology, 2025)
Non-alcoholic fatty liver disease (NAFLD) is a multisystem metabolic disorder, marked by abnormal lipid accumulation and intricate inter-organ interactions, which contribute to systemic metabolic imbalances. NAFLD may progress through several stages, including simple steatosis (NAFL), non-alcoholic steatohepatitis (NASH), cirrhosis, and potentially liver cancer. This disease is closely associated with metabolic disorders driven by overnutrition, with key pathological processes including lipid dysregulation, impaired lipid autophagy, mitochondrial dysfunction, endoplasmic reticulum (ER) stress, and local inflammation. While hepatic lipid metabolism in NAFLD is well-documented, further research into inter-organ communication mechanisms is crucial for a deeper understanding of NAFLD progression. This review delves into intrahepatic networks and tissue-specific signaling mediators involved in NAFLD pathogenesis, emphasizing their impact on distal organs.